UPAYA GURU DALAM MENGEMBANGKAN BAHASA ANAK MELALUI BUKU CERITA BERGAMBAR DI TAMAN KANAK-KANAK TK AL MAHASIN - I'in Anggryani; Erni Munastiwi (Jurnal Golden Age, 2022)
Many educational institutions apply the development of children's language through the media of simple story books. It is known that storybook media for children can encourage children's language development by creating media that attract children's interest. This study aims to determine the efforts of educators in developing children's language through picture story books at Al Mahasin Kindergarten. Research methodology: this type of qualitative research with a descriptive approach, the subject of research is educators. Data collection techniques, namely: 1) observation, 2) interviews, 3) documentation. Data analysis techniques, namely data collection, data reduction, data presentation, and conclusions. Test the validity of the data by seeing that there is no difference between what the researcher got and what actually happened. The institution has implemented this activity, but it is not optimal, so there are still many children who feel bored when stories are presented and there are still children who do not like story books. Researchers are here to provide suggestions so that children can listen to stories well and  strive for children to like books.